Bilateral Double-Pigtail Ureteral Stent Placement for Management of Ureteral Obstruction Secondary to Transitional Cell Carcinoma in a Dog - Wittmaack, Monica Carolina Nery; Sembenelli, Guilherme; Moraes, Paola Castro; Gonçalves Dias, Luís Gustavo Gosuen; Silva, Paloma Espirito Santo; Mani, Cynthia Bueno (Acta Scientiae Veterinariae, 2020)
Background: Transitional cell carcinoma (TCC) usually affects the trigone region of the bladder and proximal portion of the urethra. TCC in dogs is often complicated by local tumor invasion and obstruction of the urethra, ureters, or both. Urinary obstruction is the cause of death in approximately 60% of dogs with TCC. Radical surgeries are associated with morbidity and mortality rates. Stents have recently been evaluated for use in dogs with ureteral obstruction resulting from a variety of urinary tract tumors. This report aims to describe bilateral ureteral stent placement for treatment of malignant ureteral obstruction and long-term follow-up in a dog. Case: An 11‐year‐old female spayed Maltese with ureteral obstruction secondary to transitional cell carcinoma (TCC) in the bladder trigone. After palliative debulking procedure and diagnostic of TCC in bladder and NSAIDs treatment, recurrence has occurred causing ureteral obstruction and TCC had invaded the abdominal wall. Abdominal wall local tumor resection, trigone mass debulking and bilateral ureteral stent placement was made. A double-pigtail ureteral stent of appropriate length was advanced to bypass the ureteral obstruction. Stent sizes were 3.5 Fr in diameter and from 8 to 32 cm in length. The patient underwent surgical resection of the transitional cell carcinoma in the abdominal wall. The correct location of the bilateral ureteral pigtail stent was certified by abdominal radiography. Recovery was uneventful and the dog was discharged 2 days after surgery. Eleven months after stent placement, the dog developed lumbar vertebrae metastasis, without evidence of recurrent ureteral obstruction. The owners elected euthanasia 517 days after original presentation and 337 days after ureteral stent placement. Euthanasia was unrelated to the local tumor obstruction but was related to the bone metastasis. Discussion: Ureteral stent placement is feasible techniques for treatment of bladder TCC in dogs, with the objective of delaying the evolution of the disease and preventing ureteral obstruction. According to previous studies, although distant metastatic disease is worrisome, in the majority of dogs with bladder TCC, the primary location of the tumor is the most common cause of death. In patients with ureteral obstruction, early intervention preserves functional renal tissue. Thus, relief of obstruction should be recommended as soon as possible before irreversible renal damage occurs. The authors encourage aggressive and timely intervention, particularly when ureteral obstruction is bilateral. In the present report, 90 days postoperatively local recurrence causing ureteral obstruction was not evidenced on bladder ultrasound images and laboratory test follow-up. After this period, until 180 days after debulking surgery, tumor recurrence occurred, causing clinical signs and compromising renal function. Complications associated with stent placement included stent migration, recurrent ureteral obstruction, stranguria/pollakiuria, presumably due to irritation of the trigonal region from the distal stent; imperfect stent location; ureteral trauma during stent placement; and urinary tract infection. In the present report, the ureteral stents were placed for palliative treatment for malignant ureteral obstructions. Although urinary tract infection was recurrent, other complications associated with bilateral ureteral stent did not occur, such as accidental dislocation or stent obstruction by the tumor. The results obtained were satisfactory for urinary tract obstruction, allowing survival of 517 days. These findings may support long-term ureteral stenting in veterinary patients.